2005
DOI: 10.1126/science.1119387
|View full text |Cite
|
Sign up to set email alerts
|

Cassini Discovers a Kinematic Spiral Ring Around Saturn

Abstract: Since the time of the Voyager flybys of Saturn in 1980–1981, Saturn's eccentric F ring has been known to be accompanied on either side by faint strands of material. New Cassini observations show that these strands, initially interpreted as concentric ring segments, are in fact connected and form a single one-arm trailing spiral winding at least three times around Saturn. The spiral rotates around Saturn with the orbital motion of its constituent particles. This structure is likely the result of differential or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 16 publications
1
66
0
Order By: Relevance
“…We think that we solve in the present paper the problem raised in Charnoz et al (2005) that needed Prometheus-sized moons to create jets and spirals. In the vision we propose here, that is basically the same as in Cuzzi and Burns (1988), the F-ring core destroys, feeds, and scatters the surrounding clump (or moonlet) population.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We think that we solve in the present paper the problem raised in Charnoz et al (2005) that needed Prometheus-sized moons to create jets and spirals. In the vision we propose here, that is basically the same as in Cuzzi and Burns (1988), the F-ring core destroys, feeds, and scatters the surrounding clump (or moonlet) population.…”
Section: Discussionmentioning
confidence: 92%
“…At the intersection of these spirals with the F-ring core, smaller chaotic structures of scattered material called "jets" are observed Murray et al, 2008). All these structures are bright at high phase angles so may be mainly composed of dust (Showalter et al, 1992;Charnoz et al, 2005). E-mail address: charnoz@cea.fr.…”
Section: Introductionmentioning
confidence: 96%
“…6 As seen in Figure 21, S6's orbit came within about 1.5 km of the F-ring core, less than its estimated vertical thickness (Bosh et al 2002), in 2005 April. It would be surprising if such an interaction resulted in no observable consequences; indeed, Charnoz et al (2005) suggest that a newly discovered spiral structure observed in the tenuous material surrounding the F ring may be among those consequences. Differential precession of the node would also imply that the orbits of S/2004 S6 and S/2004 S3 must periodically intersect one another.…”
Section: F-ring Objectsmentioning
confidence: 99%
“…Whenever the organizing periodic orbit closes after more than one full turn of the secondary, the ring displays non-independent multiple components, reflecting the shape of the organizing periodic or quasi-periodic orbit in the rotating frame. Despite the fact that we have considered only planar motion, and that this is again only a qualitative comparison, the generalization of these "higher periodic" orbits to a non-planar case serves as an interpretation of recent observational findings (Charnoz et al 2005). Moreover, preliminary results (L. Benet and O. Merlo in preparation) show that our theory can also yield other observed properties of narrow rings, such as arcs qualitatively similar to those of Neptune (Namouni and Porco 2002).…”
Section: Discussionmentioning
confidence: 52%